Cerebral venous sinus thrombosis and skull base osteomyelitis as manifestations of cat‐scratch disease in a pediatric patient: A case report and literature review - Ayodeji Otufowora; Christine Lee; Aneeb Mohideen; Grace DeSena; Charlene Pringle; Freddie Guyer; Priya Sharma; Torrey Baines; Silvana Carr (Clinical Case Reports, 2023)
Key Clinical Message Cat‐scratch disease (CSD) is caused by Bartonella henselae and usually presents with regional lymphadenopathy. Skull base osteomyelitis and cerebral venous sinus thrombosis are rarely reported, particularly in immunocompetent children. CSD should be considered in the differential diagnosis of any patient with persistent headaches in the setting of cat exposure.